You are on page 1of 34

# Lecture 1

Complex Numbers
Denitions.
Let i
2
= 1.
i =

1.
Complex numbers are often denoted by z.
Just as R is the set of real numbers, C is the set of complex numbers. If z is a complex
number, z is of the form
z = x + iy C, for some x, y R.
e.g. 3 + 4i is a complex number.
z = x + iy

real part imaginary part.
If z = x + iy, x, y R,
the real part of z = (z) = Re(z) = x
the imaginary part of z = (z) = Im(z) = y.
eg. z = 3 + 4i
(z) = 3
(z) = 4.
If z = x + iy, then z (z bar) is given by
z = x iy
and is called the complex conjugate of z.
eg. If z = 3 + 4i, then z = 3 4i.
Example. Solve x
2
2x + 3 = 0.
x =
(2)

(2)
2
4(1)(3)
2(1)
=
2

8
2
=
22

2
2
= 1

2 i.
Lecture 2
Complex Arithmetic.
Example 1. (2 + 3i) + (4 + i) = 6 + 4i.
Example 2. (8 3i) (2 + 4i) = 10 7i.
Multiplication/Division.
Example 1. (2 + 3i)(1 + 2i) = 2 + 4i + 3i 6 = 4 + 7i
Example 2. (3 2i)(3 + 2i) = 9 (2i)
2
= 9 + 4 = 13
when we multiply two complex conjugates, we get a real number.
Example 3.
2+3i
1+4i
=
2+3i
1+4i

14i
14i
=
(2+3i)(14i)
(1+4i)(14i)
=
28i+3i12i
2
1(4i)
2
=
145i
17
(realising the denominator)
Lecture 3
Theorem. If two complex numbers are equal then their real parts are equal and their
imaginary parts are equal, i.e., if a +ib = c +id where a, b, c, d R, then a = c and b = d.
Example 1. Find x, y if (3 + 4i)
2
2(x iy) = x + iy.
Left hand side (LHS) = 9 16 + 24i 2x + i2y
= 7 2x + i(24 + 2y)
7 2x = x
3x = 7
x =
7
3
& 24 + 2y = y
y = 24
Example 2. Find x, y if
x
1 + i
+
y
2 i
= 2 + 4i.
LHS =
x
1 + i
+
y
2 i
=
x
1 + i

1 i
1 i
+
y
2 i

2 + i
2 + i
=
x(1 i)
1 + 1
+
y(2 + i)
4 + 1
=
x(1 i)
2
+
y(2 + i)
5
Now
x(1 i)
2
+
y(2 + i)
5
= 2 + 4i.
5x(1 i) + 2y(2 + i) = 20 + 40i
5x i5x + 4y + i2y = 20 + 40i
5x + 4y + i(5x + 2y) = 20 + 40i
Equating real and imaginary part,
5x + 4y = 20
5x + 2y = 40
Solving simultaneously,
6y = 60
y = 10
& x = 4.
Lecture 4
Square Roots of Complex Numbers.
Example 1. Find the square root of 35 12i.
Let

35 12i = a + ib : square both sides.
35 12i = (a + ib)
2
= a
2
b
2
+ i(2ab)
a
2
b
2
= 35
and 2ab = 12
ab = 6.
By inspection, solutions are a = 6& b = 1 or a = 6 or b = 1.
or a
2
b
2
= 35
ab = 6
b =
6
a
.
a
2

6
a

2
= 35
a
2

36
a
2
= 35.
a
4
36 = 35a
2
a
4
35a
2
36 = 0.
(a
2
36)(a
2
+ 1) = 0
a
2
= 36 & a
2
+ 1 = 0 a / R
a = 6 & b = 1.
&

## 35 12i = 6 i. (By convention, sign('(

z)) = sign('(z)))
Example 2. Find the roots of z
2
(1 i)z + 7i 4 = 0 in the form a + ib.
z =
(1 i)

(1 i)
2
4(1)(7i 4)
2
=
(1 i)

1 1 2i 28i + 16
2
=
(1 i)

16 30i
2
From beside,
=
(1 i) (5 3i)
2
=
1 i + 5 3i
2
or
1 i (5 3i)
2
= 3 2i or 2 + i.

16 30i = (a + ib)
16 30i = a
2
b
2
+ i(2ab)
a
2
b
2
= 16
2ab = 30
ab = 15
a = 5 & b = 3
or a = 5 & b = 3
&

16 30i = 5 3i
sign(16) = sign(5) = +
Lecture 5
The Argand Diagram. (Note: Ordered pairs:- eg. 2 + i = (2, 1)
for 2 + i = x + iy on (x, y)-plane)
Two methods: i. P(x, y) the point P on the (x, y)-plane
ii. Vector

OP
x-axis is called the real axis.
y-axis is called the imaginary axis.
Eg. Plot the following on the Argand diagram:
P = 2 + 3i; B = 3 i; A = 2 i; M = 4; E = 2i
z = x + iy
= r cos + ir sin
= r(cos + i sin)
Modulus (Distance OP)
denoted by r, mod z, [z[, [x + iy[
by Pythagoras, r
2
= x
2
+ y
2
r =

x
2
+ y
2
r = [z[ = [x + iy[ =

x
2
+ y
2
.
Argument (angle )
denoted by , arg z, arg(x + iy) [or amp z, amp (x + iy) amplitude]
by denition, 180

< 180

For x ,= 0, tan =
y
x
.
The mod-arg form of a complex number
z = x + iy
= r(cos + i sin)
( = r cis ).
Complex Conjugate
If z = x + iy, then the complex conjugate is z = x iy
eg. 360

c
= 2
180

=
90

=

2
60

=

3
45

=

4
30

=

6
More on mod-arg forms.
Examples. Express the following in mod-arg form:-
(a) 2 + 2i;(b) 2 + 5i;(c) 1 +

3i;(d) 3i;(e) 1 3i
(a) 2 + 2i
r =

2
2
+ 2
2
=

8 = 2

2
& tan =
2
2
= 1 & =

4
& 2 + 2i = 2

cos

4
+ i sin

4

.
(b) 2 + 5i
r =

2
2
+ 5
2
=

29
& tan =
5
2
& = tan
1 5
2
68

12

& 2 + 5i =

29

cos

tan
1 5
2

+ i sin

tan
1 5
2

29

cos 68

12

+ i sin68

12

(c) 1 +

3i
r =

1
2
+ 3 =

4 = 2
tan =

3
1
& =

3
& =

3
=
2
3
& 1 +

3i = 2

cos
2
3
+ i sin
2
3

.
(d) 3i
By inspection, 3i = 3

cos

2
+ i sin

2

.
(e) 1 3i
r =

1
2
+ 3
2
=

10
tan() = 3 & = tan
1
3 & = tan
1
3 71

34

.
& 1 3i =

10

cos

tan
1
3

+ i sin

tan
1
3

10

cos

tan
1
3

i sin

tan
1
3

10

cos 71

34

i sin71

34

.
Lecture 6
Axioms
An integral domain is a set of elements with two binary operations dened for them, which
obey the laws obeyed by the integers.
A set S is an integral domain if its elements a, b, c, . . . obey the following laws.
1. Closure Law for Addition, i.e., a + b S
2. Closure Law for Multiplication, i.e., a b S
3. Commutative Law for Addition, i.e., a + b = b + a
4. Commutative Law for Multiplication, i.e., a b = b a
5. Associative Law for Addition, i.e., a + (b + c) = (a + b) + c
6. Associative Law for Multiplication, i.e., a (b c) = (a b) c
7. Distributive Law of Multiplication over Addition, i.e., a (b + c) = a b + a c
8. There exists an additive identity (or zero element) 0, such that for every a,
a + 0 = 0 + a = a (Note 0 S)
9. There exists a multiplicative identity (or unity element) 1, such that for every a,
a 1 = 1 a = a (Note 1 S)
10. There exists an additive inverse (or opposite), a, for each member a of the set such
that a + (a) = (a) + a = 0.
11. Cancellation Law. If ab = ac and a = 0, then b = c.
Example 1. Z, the set of the integers, is an integral domain.
The elements of a eld F obey the above axioms 1-10 for integral domains, (where a, b, c
are elements of F) and instead of the cancellation law, there is a law about the existence
of a multiplicative inverse (or reciprocal):
11

. If a
1
and 1 are elements of F, and a a
1
= a
1
a = 1, where a = 0, then a
1
is
the multiplicative inverse of a.
Example 2. C, the set of complex numbers is a eld.
Example 3. The additive inverse of z = 2 + 3i is z = 2 3i
Example 4. The multiplicative inverse of z = 2 + 3i is z
1
=
1
2+3i
=
1
2+3i

23i
23i

=
23i
13
.
Lecture 7
()

## cos(A + B) = cos Acos B sinAsinB

sin(A + B) = sinAcos B + sinB cos A
Mod-arg theorems
i. If z
1
= r
1
(cos
1
+ i sin
1
) & z
2
= r
2
(cos
2
+ i sin
2
)
then if z
1
= z
2
then r
1
= r
2
&
1
=
2
.
ii. [z
1
z
2
[ = [z
1
[[z
2
[ and arg(z
1
z
2
) = arg z
1
+ arg z
2
2.
i.e., for example:
arg(z
1
z
2
) = 100

+ 140

360

= 120

arg

z
1
z
2

= arg z
1
arg z
2
2.
Proof . If z
1
= r
1
(cos
1
+ i sin
1
)
and z
2
= r
2
(cos
2
+ i sin
2
)
then z
1
z
2
= r
1
(cos
1
+ i sin
1
) r
2
(cos
2
+ i sin
2
)
= r
1
r
2
(cos
1
cos
2
sin
1
sin
2
+ i sin
2
cos
1
+ i sin
1
cos
2
)
= r
1
r
2
(cos(
1
+
2
) + i sin(
1
+
2
)) (see () above)
& [z
1
z
2
[ = r
1
r
2
= [z
1
[[z
2
[ and arg(z
1
z
2
) =
1
+
2
= arg(z
1
) + arg(z
2
).
Extended:
arg(z
1
z
2
z
n
) = arg z
1
+ arg z
2
+ + arg z
n
2n.
[z
n
[ = [z[
n
(eg., [z
3
[ = [zzz[ = [z[[z[[z[ = [z[
3
).
and arg(z
n
) = narg z 2k.

1
z
n

=
1
|z|
n
and arg

1
z
n

= arg 1 arg(z
n
) = 0 narg z 2k = narg z 2k.
Example 1. Find the modulus and argument of z = (2 i)(1 3i).
[z[ = [2 i[[1 3i[
=

2
2
+ 1
2

1
2
+ 3
2
=

10
=

50
= 5

2.
arg(z) = arg(2 i) + arg(1 3i) = tan
1 1
2
tan
1
3 98

.
Example 2. z =
(1 + 2i)(1 + i)
2 3i
[z[ =
[ 1 + 2i[[1 + i[
[ 2 3i[
=

13
=

10

13
=

10
13
.
arg(z) = arg(1 + 2i) + arg(1 + i) arg(2 3i)
285

15

360

= 74

45

Lecture 8
Triangle Inequalities.
Example 1. If z
1
= 2 + i and z
2
= 1 + 2i, z
1
+ z
2
= 1 + 3i.
Polygon Rule.
Subtraction of Complex Numbers.
z
2
z
1
= z
2
+ (z
1
):
Triangle Inequalities.
[z
1
+ z
2
[ [z
1
[ +[z
2
[:
[z
1
z
2
[ [z
1
[ [z
2
[:
Example 2. Verify the triangle inequalities if
z
1
= 2 3i,
z
2
= 1 + 4i,
z
1
+ z
2
= 1 + i,
z
1
z
2
= 3 7i.
[z
1
[ =

13
[z
2
[ =

17
[z
1
+ z
2
[ =

2
[z
1
z
2
[ =

58.
[z
1
+ z
2
[ [z
1
[ +[z
2
[

13 +

17
[z
1
z
2
[ [z
1
[ [z
2
[

58

13

17 .
triangle inequalities hold.
Product of Complex Numbers.
The triangle OQR is constructed similar to AOP. A is the point (1, 0).
Multiplication by i, 1, i.
Multiplication by i, rotation 90

(anticlockwise).
Multiplication by 1, rotation 180

anticlockwise.
Multiplication by i, rotation 270

anticlockwise
Lecture 9
Geometric Representation of Locus Problems.
General forms:- |z z
1
| = a represents a circle, centre at z
1
Example 1. |z| = 1.
Example 2. |z 3| = 2.
Example 3. |z i| = 1.
Example 4. |z 1 2i| = 2
|z (1 + 2i)| = 2 centre (1, 2), radius 2 units.
Example 5. |z| 3 (note:- if less than, it is inside, if it is greater than, it is outside.)
Example 6. 2 < |z| 3.
Example 7. |z| 4 and 0 arg z

3
.
Example 8. 1 (z) 2 if z = x + iy,
then (z) = y (& 1 y 2)
Example 9.

6
< arg z

3
.
Example 10. 1 (z) 2 and (z) 1
Example 11. 1 (z) 2 or (z) 1
Example 12. |z| 4 or 0 arg z

3
Lecture 10
Using Algebra to Represent Locus Problems
Example 1. Show algebraically that |z 2 i| = 4 represents a circle with radius 4 units
and centre (2, 1).
|z 2 i| = 4.
|x + iy 2 i| = 4.
|(x 2) + i(y 1)| = 4.

(x 2)
2
+ (y 1)
2
= 4.
(x 2)
2
+ (y 1)
2
= 16.
which is a circle centre (2, 1), radius 4 units.
Example 2. Sketch the curve: (i) (z
2
) = 3 (ii) (z
2
) = 4.
(i)
(z
2
) = 3
((x + iy)
2
) = 3
(x
2
y
2
+ 2ixy) = 3
x
2
y
2
= 3.
(ii)
(z
2
) = 4.
2xy = 4.
xy = 2.
Example 3. Describe in geometric terms, the curve described by 2|z| = z + z + 4.
2|z| = z + z + 4.
2|x + iy| = x + iy + x iy + 4.
2

x
2
+ y
2
= 2x + 4 = 2(x + 2).

x
2
+ y
2
= x + 2.
x
2
+ y
2
= (x + 2)
2
.
x
2
+ y
2
= x
2
+ 4x + 4.
y
2
= 4x + 4.
sideways parabola at vertex (1, 0).
Example 4. Sketch the locus of (z + iz) < 2.
(x + iy + i(x + iy)) < 2.
(x + iy + ix y) < 2.
x y < 2.
Example 5. If z
1
= 1 + i & z
2
= 2 + 3i nd the locus of z if |z z
1
| = |z z
2
|.
|x + iy (1 + i)| = |x + iy (2 + 3i)|.
|(x 1) + i(y 1)| = |(x 2) + i(y 3)|.

(x 1)
2
+ (y 1)
2
=

(x 2)
2
+ (y 3)
2
.
(x 1)
2
+ (y 1)
2
= (x 2)
2
+ (y 3)
2
.
x
2
2x + 1 + y
2
2y + 1 = x
2
4x + 4 + y
2
6y + 9.
2x + 4y = 11.
N.B. |z z
1
| = |z z
2
| will always be a straight line. It will always be the perpendicular
bisector of the interval joining z
1
to z
2
.
Lecture 11
() Note. sin(A+B) = sinAcos B+sinB cos A & cos(A+B) = cos Acos BsinAsinB.
De Moivres Theorem. (cos + i sin)
n
= cos n + i sinn.
Proof. (By mathematical induction for n = 0, 1, 2, . . . .)
Step 1. Test n = 0.
L.H.S. = (cos + i sin)
0
= 1
R.H.S. = cos 0 + i sin0
= 1
= L.H.S.
it is true for n = 0.
Step 2. Assume true for n = k i.e., (cos + i sin)
k
= cos k + i sink.
Test for n = k + 1.
i.e., L.H.S. = (cos + i sin)
k+1
& R.H.S. = cos(k + 1) + i sin(k + 1)
= (cos + i sin)
k
(cos + i sin)
1
= (cos k + i sink)(cos + i sin)(since we have assumed it true for n = k)
= cos k cos + i sin cos k + i sink cos sink sin
= cos k cos sink sin + i(sin cos k + sink cos )
= cos(k + ) + i sin(k + ) (see () above)
= cos(k + 1) + i sin(k + 1)
= R.H.S.
Step 3. If the result is true for n = 0, then true for n = 0 + 1, i.e., n = 1. If the result is
true for n = 1, then true for n = 1 + 1, i.e., n = 2 ans so on for all nonnegative integers
n
Example 1. Simplify:
(a) (cos i sin)
4
(b) (sin i cos )
7
(c)
(cos 2+i sin 2)
3
(cos i sin )
4
.
(a) (cos i sin)
4
= cos(4) i sin(4)
= cos 4 + i sin4
(b) (sin i cos )
7
= (i cos + sin)
7
= i
7
(cos i sin)
7
= i(cos 7 i sin7)
= sin7 + i cos 7
(c)
(cos 2+i sin 2)
3
(cos i sin )
4
=
(cos +i sin )
6
(cos i sin )
4
=
(cos +i sin )
6
(cos()+i sin())
4
=
(cos +i sin )
6
(cos +i sin )
4
= (cos + i sin)
10
= cos 10 + i sin10
Example 2. Express in the form x + iy:
(a)

cos

2
+ i sin

2

6
(b)

1 +

3

10
.
(a) (cos

2
+ i sin

2
)
6
= cos
6
2
+ i sin
6
2
= cos 3 + i sin3
= 1 + 0i
= 1
(b) (1 +

3)
10
= (2(cos

3
+ i sin

3
)
10
= 2
10
(cos
10
3
+ i sin
10
3
)
= 2
10

1
2
i

3
2

= 512 512i

3
Lecture 12
De Moivres Theorem and the Argand Diagram
Example. If z =

## 3 + i represent the following on the Argand Diagram:

z, iz,
1
z
, z, 2z, z, z
2
+ z, z
3
z
z = 2(cos

6
+ i sin

6
)
z
1
= (2(cos

6
+ i sin

6
))
1
=
1
2
(cos

6
+ i sin

6
)
=
1
2
(cos

6
i sin

6
)
2z = 4(cos

6
+ i sin

6
)
z
2
= (2(cos

6
+ i sin

6
))
2
= 4(cos

3
+ i sin

3
)
z
3
= (2(cos

6
+ i sin

6
))
3
= 8(cos

2
+ i sin

2
)
Solution on next page.
Lecture 13
Trigonometric Identities and DeMoivres Theorem
Example. Obtain cos 6 in terms of cos . Hence show that x = cos(2k + 1)

12
where
k = 0, 1, 2, 3, 4, 5 is a solution to the equation 32x
6
48x
4
+18x
2
1 = 0 and hence deduce
that cos

12
. cos
5
12
=
1
4
.
cos 6 + i sin6 = (cos + i sin)
6
.
Consider using Pascals Triangle:
1
1 1
1 2 1
1 3 3 1
1 4 6 4 1
1 5 10 10 5 1
1 6 15 20 15 6 1
. . . . . . . . . . . . . . . . . .
For example,
(a + b)
2
= a
2
+ 2ab + b
2
(a + b)
3
= a
3
+ 3a
2
b + 3ab
2
+ b
3
(a + b)
4
= a
4
+ 4a
3
b + 6a
2
b
2
+ 4ab
3
+ b
4
(a + b)
5
= a
5
+ 5a
4
b + 10a
3
b
2
+ 10a
2
b
3
+ 5ab
4
+ b
5
(a + b)
6
= a
6
+ 6a
5
b + 15a
4
b
2
+ 20a
3
b
3
+ 15a
2
b
4
+ 6ab
5
+ b
6
cos 6 + i sin = (cos + i sin)
6
= cos
6
+ 6 cos
5
i sin + 15 cos
4
(i sin)
2
+ 20 cos
3
(i sin)
3
+ 15 cos
2
(i sin)
4
+6 cos (i sin)
5
+ (i sin)
6
- from Pascals Triangle
= cos
6
+ 6i cos
5
sin 15 cos
4
sin
2
20i cos
3
sin
3
+ 15 cos
2
sin
4
+ 6i cos sin
5

sin
6

cos 6 = cos
6
15 cos
4
sin
2
+ 15 cos
2
sin
4
sin
6
equating parts
= cos
6
15 cos
4
(1 cos
2
) + 15 cos
2
(1 cos
2
)
2
(1 cos
2
)
3
= cos
6
15 cos
4
+ 15 cos
6
+ 15 cos
2
(1 2 cos
2
+ cos
4
)
(1 3 cos
2
+ 3 cos
4
cos
6
)
= cos
6
15 cos
4
+ 15 cos
6
+ 15 cos
2
30 cos
4
+ 15 cos
6
1 + 3 cos
2

3 cos
4
+ cos
6

= 32 cos
6
48 cos
4
+ 18 cos
2
1
If cos 6 = 0, then 6 =

2
,
3
2
,
5
2
,
7
2
,
9
2
, etc.
=

12
,
3
12
,
5
12
,
7
12
,
9
12
, etc.
=
2k+1
12
for k = 0, 1, 2, 3, 4, 5, . . .
these are the roots of 32 cos
6
48 cos
4
+ 18 cos
2
1 = 0.
Now if x = cos , then 32x
6
48x
4
+ 18x
2
1 = 0 has roots
x = cos

12
, cos
3
12
, cos
5
12
, cos
7
12
, cos
9
12
, cos
11
12
= cos
2k+1
12
for k = 0, 1, 2, 3, 4, 5 (six roots because we have degree six).
Product of roots of 32x
6
48x
4
+ 18x
2
1 = 0 is
1
32
.
cos

12
cos
3
12
cos
5
12
cos
7
12
cos
9
12
cos
11
12
=
1
32
cos

12

1

2
cos
5
12
cos
7
12
(
1

2
) cos
11
12
=
1
32
cos

12
cos
5
12
cos
7
12
cos
11
12
=
1
16
But cos
11
12
= cos

12
and cos
7
12
= cos
5
12
.
cos
2
12
cos
2 5
12
=
1
16
cos

12
cos
5
12
=
1
4

Lecture 14
Example. If z = cos + i sin, show that z
n
+
1
z
n
= 2 cos n. Hence or otherwise obtain
an expression for cos
5
in terms of cos n and then evaluate

2
0
cos
5
d.
z = cos + i sin
z
n
= (cos + i sin)
n
= cos n + i sinn
1
z
n
= z
n
= (cos + i sin)
n
= cos n + i sinn
= cos n i sinn.
z
n
+
1
z
n
= (cos n + i sinn) + (cos n i sinn)
= 2 cos n.
Pascals :
1
1 1
1 2 1
1 3 3 1
1 4 6 4 1
1 5 10 10 5 1

z +
1
z

5
= z
5
+ 5z
4

1
z

+ 10z
3

1
z

2
+ 10z
2

1
z

3
+ 5z

1
z

4
+

1
z

5
= z
5
+ 5z
3
+ 10z +
10
z
+
5
z
3
+
1
z
5
= z
5
+
1
z
5
+ 5

z
3
+
1
z
3

+ 10

z +
1
z

Now : z
n
+
1
z
n
= 2 cos n.
z +
1
z
= 2 cos ,
z
3
+
1
z
3
= 2 cos 3,
& z
5
+
1
z
5
= 2 cos 5.
(2 cos )
5
= 2 cos 5 + 5 2 cos 3 + 10 2 cos
32 cos
5
= 2 cos 5 + 10 cos 3 + 20 cos
cos
5
=
1
32

## 2 cos 5 + 10 cos 3 + 20 cos

=
1
16
(cos 5 + 5 cos 3 + 10 cos )
&

2
0
cos
5
d =
1
16

2
0
(cos 5 + 5 cos 3 + 10 cos ) d
=
1
16

sin 5
5
+
5
3
sin3 + 10 sin

2
0
=
1
16

1
5
sin
5
2
+
5
2
sin
3
2
+ 10 sin

2

=
1
16

1
5

5
3
+ 10

=
8
15

N.B. Similar expressions can be found for sin
5
:
z
n

1
z
n
= (cos n + i sinn) (cos n i sinn)
= 2i sinn.

z
1
z

5
= z
5
5 z
4

1
z
+ 10z
3

1
z

2
10z
2

1
z

3
+ 5z

1
z

1
z

5
=

z
5

1
z
5

z
3

1
z
3

+ 10

z
1
z

(2i sin)
5
= 2i sin5 5 2i sin3 + 10 2i sin
32i
5
sin
5
= 2i sin5 10i sin3 + 20i sin (Note : i
5
= i)
sin
5
=
1
32
(2 sin5 10 sin3 + 20 sin) (dividing by 32i)
=
1
16
(sin5 5 sin3 + 10 sin)

&

sin
5
d=
1
16

## (sin55 sin3+10 sin) d=

1
16

1
5
cos 5+
5
3
cos 310 cos )+C)
Lecture 15
Complex Roots of Unity.
If z
n
= 1 has n roots, all lying on the unit circle in the argand diagram evenly spaced,
for example:
For z
n
= 1:
n is odd, 1 real root and n 1 non-real complex roots.
n even, 2 real roots, n 2 non-real complex roots.
z
n
= 1 has n complex roots.
Example. Solve z
7
= 1 and show the roots on the argand diagram. Hence show that
cos
2
7
+ cos
4
7
+ cos
6
7
=
1
2
.
If z = cos + i sin (modulus 1 because |z
7
| = |z|
7
= 1 & |z| = 1),
z
7
= (cos + i sin)
7
= 1
= cos 7 + i sin7 = 1.
Equating real parts,
cos 7 = 1
7 = 0, 2, 4, 6, 8, 10, 12, . . .
= 0,
2
7
,
4
7
,
6
7
,
8
7
,
10
7
,
12
7
, . . .
roots are z
1
= cos 0 + i sin0 = 1
z
2
= cos
2
7
+ i sin
2
7
=
z
3
= cos
4
7
+ i sin
4
7
=
2
z
4
= cos
6
7
+ i sin
6
7
=
3
z
5
= cos
8
7
+ i sin
8
7
=
4
z
6
= cos
10
7
+ i sin
10
7
=
5
z
7
= cos
12
7
+ i sin
12
7
=
6
(7 solutions because degree of polynomial equation z
7
= 1 is 7.)
cos
8
7
= cos
6
7
sin
8
7
= sin
6
7
cos
10
7
= cos
4
7
sin
10
7
= sin
4
7
cos
12
7
= cos
2
7
sin
12
7
= sin
2
7
.
& the roots for < arg z , are :
z
1
= 1
z
2
= cos
2
7
+ i sin
2
7
= z
7
=
z
3
= cos
4
7
+ i sin
4
7
= z
6
=
2
z
4
= cos
6
7
+ i sin
6
7
= z
5
=
3
z
5
= cos
6
7
i sin
6
7
= z
4
=
3
z
6
= cos
4
7
i sin
4
7
= z
3
=
2
z
7
= cos
2
7
i sin
2
7
= z
2
=
1
i.e., the complex roots of unity always occur as pairs
(Note: a
n
x
n
+ a
n1
x
n1
+ a
n2
x
n2
+ + a
0
= 0, then sum of roots =
b
a
.)
z
7
= 1
z
7
1 = 0
& sum of roots = 0 (since coecients of z
6
is 0.)
z
1
+ z
2
+ z
3
+ z
4
+ z
5
+ z
6
+ z
7
= 0
& 1 + 2 cos
2
7
+ 2 cos
4
7
+ 2 cos
6
7
= 0
2 cos
2
7
+ 2 cos
4
7
+ 2 cos
6
7
= 1
cos
2
7
+ cos
4
7
+ cos
6
7
=
1
2